Comparative Digital Occlusal Analysis of Different Sagittal Skeletal Malocclusions in Dravidian Subjects − A Prospective Study - Swati Singh; Ravindra Kumar Jain; Suresh Venugopalan; Aravind T.R Prasanna (Wolters Kluwer Medknow Publications, 2023)
Introduction: T-scan III is used in clinical practice for a digital assessment of occlusal force distribution and other occlusal parameters. The present study was proposed to do an assessment of occlusal contacts and forces using T-scan III in subjects with class II division II malocclusion and compare it to subjects with class I malocclusion requiring fixed orthodontic treatment. Materials and Methods: This prospective study included 70 subjects − 33 in group A (Angle's class II division II malocclusion) and 37 in group B (Angle's class I malocclusion). Occlusal analysis was done with T-scan III, and parameters like occlusal force distribution (OFD), occlusion time (OT), and disocclusion time (DT) were recorded. Statistical analysis was done with SPSS software. Independent t-test for intergroup comparisons and paired t-tests for intra group comparisons were done. Results: A Significant intergroup difference in OFD between left/right, posterior/anterior regions (P < 0.05) was noted between groups. OT and DT (left lateral excursive) were also significantly higher (P < 0.05) in group A. On intergroup comparison, the L/R bite force ratio was higher in group B males (P < 0.05) and the P/A bite force ratio was higher in group B females (P < 0.05). Conclusion: In subjects with class II division II malocclusion, anterior teeth were subjected to greater occlusal loading when compared to class I subjects and had higher occlusion and disocclusion times.